2022
DOI: 10.3390/microorganisms10020459
|View full text |Cite
|
Sign up to set email alerts
|

Mycobiome-Host Coevolution? The Mycobiome of Ancestral Human Populations Seems to Be Different and Less Diverse Than Those of Extant Native and Urban-Industrialized Populations

Abstract: Few data exist on the human gut mycobiome in relation to lifestyle, ethnicity, and dietary habits. To understand the effect of these factors on the structure of the human gut mycobiome, we analyzed sequences belonging to two extinct pre-Columbian cultures inhabiting Puerto Rico (the Huecoid and Saladoid) and compared them to coprolite samples found in Mexico and Ötzi, the Iceman’s large intestine. Stool mycobiome samples from extant populations in Peru and urban cultures from the United States were also includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 88 publications
(140 reference statements)
2
4
0
Order By: Relevance
“…Similar dietary components among the Mazahua and United States feces, and to a lesser extent the Tunapuco, may have resulted in the clustering patterns observed for the Mazahua and United States and the transitional state of the Tunapuco. These results are partially supported by a recent study showing the segregation of pre-Columbian and present-day populations based on their gut mycobiome [ 36 ]. Studies have shown that dietary lifestyles strongly shape the composition of the gut microbiome of traditional populations, which differs from that of industrialized populations [ 41 , 97 104 ].…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Similar dietary components among the Mazahua and United States feces, and to a lesser extent the Tunapuco, may have resulted in the clustering patterns observed for the Mazahua and United States and the transitional state of the Tunapuco. These results are partially supported by a recent study showing the segregation of pre-Columbian and present-day populations based on their gut mycobiome [ 36 ]. Studies have shown that dietary lifestyles strongly shape the composition of the gut microbiome of traditional populations, which differs from that of industrialized populations [ 41 , 97 104 ].…”
Section: Discussionsupporting
confidence: 74%
“…In addition to micro- and macroscopic remains, DNA analysis has revealed the diet of extinct sloths [ 24 , 25 ], dogs [ 26 , 27 ], moas [ 28 , 29 ], and mummies [ 30 , 31 ]. Moreover, the reconstruction of ancient human diets has been possible in part by studies of the gut microbiome [ 32 , 33 ], virome [ 34 ], parasitome [ 35 ], and mycobiome [ 36 ] found in coprolites. Notably, ancient microbial communities detected in coprolites can also reflect the evolution of human lifestyles through time [ 23 , 36 38 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These fungi develop important interdependent relationships with the bacteria present in the gut, developing mutualism to provide the best environment for host survival [ 32 ]. Factors such as diet, genetics, and lifestyle greatly impact one’s mycobiome and its development over time [ 33 ]. Disrupting the fungal environment has been shown to cause irritable bowel syndrome, coeliac disease, and pancreatic disorders, displaying the importance that these fungi play in maintaining one’s health [ 34 ].…”
Section: Gut Mycobiomementioning
confidence: 99%
“…The study of ancient microorganisms, applied to humans, helps to reconstruct the evolution of populations based on their lifestyle and environment and on contact with infectious agents and related diseases [1][2][3][4]. This assumption applies very well to the study of the human microbiome, in particular the oral one, detectable in ancient dental remains [5][6][7].…”
Section: Introductionmentioning
confidence: 99%